2012
DOI: 10.1158/1055-9965.epi-12-0611
|View full text |Cite
|
Sign up to set email alerts
|

High-Sensitivity C-Reactive Protein Levels and Cancer Mortality

Abstract: Background: High-sensitivity C-reactive protein (hs-CRP) is an important inflammatory marker, and inflammation is known to be involved in the initiation and progression of cancer. We investigated the association between serum hs-CRP levels and all-cause mortality, cancer mortality, and site-specific cancer mortality in apparently cancer-free Koreans.Methods: A total of 33,567 participants who underwent routine check-ups at a single tertiary hospital healthscreening center between May 1995 and December 2006, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 35 publications
2
47
0
Order By: Relevance
“…Indeed, one study reported that among individuals with less than “very good” self-rated health, men were more likely to die from cancer and also heart disease than women (Benjamins et al, 2004)—and both of these conditions are also associated with elevated hs-CRP (e.g., Ko et al, 2012; Ridker, 2007; Shah et al, 2009). …”
Section: Bmi and Sex Differentiated Srh-crp Associations In Young Adultsmentioning
confidence: 99%
“…Indeed, one study reported that among individuals with less than “very good” self-rated health, men were more likely to die from cancer and also heart disease than women (Benjamins et al, 2004)—and both of these conditions are also associated with elevated hs-CRP (e.g., Ko et al, 2012; Ridker, 2007; Shah et al, 2009). …”
Section: Bmi and Sex Differentiated Srh-crp Associations In Young Adultsmentioning
confidence: 99%
“…In several prospective studies, elevated markers of systemic inflammation have been repeatedly associated with a decline in lung function in young adults [17][18][19] and COPD in adults [20][21][22]. Similarly, in numerous prospective studies of cancer, elevated systemic markers have been associated with the development of lung cancer 5-15 years later [23][24][25][26][27]. Further evidence supporting a role for systemic inflammation in COPD and lung cancer comes from animal studies showing overexpression of IL-6 is linked to the development of COPD and that systemic inflammation in a nonsmoking murine model is linked to innate immune response-mediated DNA damage in the bronchial epithelium [28][29][30][31].…”
Section: Systemic Inflammation In the Copd-lung Cancer Linkmentioning
confidence: 99%
“…This increase in systemic inflammation may result from either an overactive bronchial epithelial response to smoking or an underlying primary hyper-immune response of the innate immune system, or both [28][29][30][31]. Support for the latter comes from studies showing systemic inflammation is linked to many cancers, where smoking (or obesity) are known risk factors, although the link is strongest for lung cancer [23][24][25][26][27]. Systemic inflammation, to varying degrees, affects between 50% and 70% of those with COPD and lung cancer [20,22,26].…”
Section: Systemic Inflammation In the Copd-lung Cancer Linkmentioning
confidence: 99%
See 1 more Smart Citation
“…He noted that there are more than 10 million dementia caregivers, and they have a 63% higher mortality risk than noncaregivers (Schulz & Beach, 1999), with some of this increased risk associated with increased inflammation (Frasure-Smith et al, 2007; Ko et al, 2012; Ridker, Hennekens, Buring, & Rifai, 2000). …”
mentioning
confidence: 99%